Glucocorticoid therapy for adrenal insufficiency: nonadherence, concerns and dissatisfaction with information. (15th February 2016) - Chapman, S.C.E.; Llahana, S.; Carroll, P.; Horne, R.
Summary: Objective: Appropriate self‐management of glucocorticoid therapy (GC) is crucial for patients with adrenal insufficiency (AI). We aimed to describe patients' self‐reported nonadherence to GC, evaluate perceived doubts about need for GC, concerns about adverse effects, and dissatisfaction with information received about GC. Design: Cross‐sectional survey. Patients: Patients prescribed GC for AI ( n = 81) from five European countries. Measurements: Online survey including the Medication Adherence Report Scale (MARS), Beliefs about Medicines Questionnaire © (BMQ Specific, adapted for AI) and Satisfaction with Information about Medicines Scale © (Prof Rob Horne; SIMS). Results: Most patients (85·2%) reported a degree of nonadherence to GC. The most frequent types of nonadherence concerned changing the timing of GC doses, for example taking a dose later in the day than advised (37·0%). Few patients doubted their personal need for daily GC, but most reported high concerns about GC including potential weight gain (50·6%), osteoporosis (53·6%) and the continuing risk of adrenal crisis (50·6%). Dissatisfaction with information about GC was frequent, with participants particularly dissatisfied with the amount of information they had received about potential problems with GC. People who expressed dissatisfaction with information about GC, and concerns about its adverse effects were also more likely to report nonadherence ( P < 0·05). Conclusions: Nonadherence to treatment, concerns about potential adverse effects and dissatisfaction with the information provided about treatment were frequently reported by this European sample of AI patients. Many AI patients may need additional information about their GC and support to address concerns about GC and facilitate adherence.